The Excessive Regulation of Early Abortion Medication in the UK: The Case for Reform. (15th December 2021) - Romanis, Elizabeth Chloe; Mullock, Alexandra; Parsons, Jordan A
Abstract: Early medical abortion (EMA) involves the administration of two medications—mifepristone and misoprostol—24–48 hours apart. These routinely used medications are recognised as safe and effective by the World Health Organization which recommends this combination of medications as a safe form of abortion until nine weeks' gestation. Despite the safety and effectiveness of this drug regimen, there exists excessive regulation around EMA. This is despite new regulations introduced in Northern Ireland in 2020 and (temporary) changes made in 2020 to allow at-home administration of mifepristone in Great Britain (following earlier changes to permit home use of misoprostol). We argue that the excessive regulation of EMA is inappropriate because it fails to recognise that abortion is essential healthcare. Further, the regulation constitutes disproportionate interference with clinical discretion and service organisation because it is medically unnecessary and prevents abortion providers in the UK from adapting their service provision in line with emerging evidence of best practice.